Microsurgical Approach to Hypertensive Deep Nuclear Bleed: Preliminary Experience and Short Term Outcome - Karki, Karuna Tamrakar; Bhattarai, Binod; Munakomi, Sunil; Chaudhary, Pramod K (Nepal Journal of Neuroscience, 2019)
Efficacy of surgical evacuation of hypertensive deep nuclear bleed with or without decompressivecraniectomy remains controversial. Our paper mainly focuses on short-term preliminary experience on the evacuation of hypertensive deep nuclear bleed via transsylvian approach in reducing secondary brain injury for better neurological outcome. In between August 2012 to October 2013, 25surgically managed patients with hypertensive deep nuclear bleed were reviewed retrospectively. Among them, 13 cases underwent transsylvianevacuation of hematoma.84.6% were males. Age ranged between 38 to68 years with a mean age of 50.23 with standard deviation of 8.29 years. The size of hematoma measured in computed tomography scan ranged from 48 to 156 ml (mean 69 ml with standard deviation 38.28 ml). Nine hypertensive patients were taking medication on an irregular basis. The remaining had never taken antihypertensive agents before the ictus. 7/15 was the lowest Glasgow Coma Scale score and 13/15 was the highest score on arrival to the emergency room. Eight cases showed near-total evacuation of hematoma on repeated scan was taken after24 hours of surgery. One patient underwent transsylvian evacuation in 2nd postoperative day after recollection following the trans frontale vacation of right putaminal bleed. Two patients died on 3rd and 4th post-operative day respectively (GOS=1). GOS score during discharge was 3 in three cases and five cases obtained score 4. Three cases obtained GOS 5.In a 3-month clinical follow-up, one case scored modified Rankin Scale 1, three cases scored 2, four cases obtained score 3, two others scored modified Rankin Scale grade 4 and one case had modified Rankin Scale 6.Transsylvian transinsular microsurgical technique safely depicts the anatomical orientation in sylvian fissure preserving the overlying eloquent cortex in frontal and temporal lobes. This aided us to achieve better surgical and neurological outcome in patients with hypertensive deep nuclear hemorrhage irrespective to the size of hematoma.